Experimental study on hydrodynamic characteristics of a taut moored floating box - Ji, Qiaoling; Jia, Xiuru; Xu, Yan; Cheng, Yu; Zhang, Guowei; Li, Zhenyu (Frontiers in Mechanical Engineering, 2025)
To investigate the hydrodynamic capabilities of the floating breakwater with a taut mooring system, a two-dimensional physical modelling experiment was performed to investigate the hydrodynamic characteristics of the hydrodynamic pressure on the front surface of the floating box, mooring line tension and transmission coefficient under regular waves, considering factors such as mooring angle, mooring line pre-tension and relative width. The results show that, with the increase of the mooring angle, the hydrodynamic pressure on the floating box first increases and then decreases, the mooring line tension first increases and then decreases slightly, and the transmission coefficient obviously decreases. As the mooring line pre-tension increases, the hydrodynamic pressure and the mooring line tension increase, and the transmission coefficient first decreases and then increases. As the relative width increases, the hydrodynamic pressure, mooring line tension and transmission coefficient all show a decreasing trend. The results can provide a reference for the design and safety assessment of taut moored single pontoon floating breakwater.